Chemical characterisation of kernels, kernel meals and oils from Jatropha cordata and Jatropha cardiophylla seeds. (23rd November 2012) - Gámez‐Meza, Nohemí; Alday‐Lara, Perla P; Makkar, Harinder PS; Becker, Klaus; Medina‐Juárez, Luis A
Abstract BACKGROUND Jatropha cordata and Jatropha cardiophylla are native to northwestern Mexico and are adapted to arid and semi‐arid conditions (<500 mm of precipitation and temperatures from 8 to 45 °C). The aim of this study was to evaluate the chemical composition of J. cordata and J. cardiophylla kernels and oils as well as antinutrients in the defatted kernel meals of these species. RESULTS Kernels of J. cordata and J. cardiophylla seeds analysed in this study were rich in crude protein (283 and 289 g kg−1 respectively) and lipid (517 and 537 g kg−1 respectively). The main fatty acids in J. cordata and J. cardiophylla oils were linoleic and oleic acids. High levels of trypsin inhibitor and phytates and low levels of saponins were present in the meals. The phorbol ester contents in J. cordata and J. cardiophylla kernel meals were 2.73 and 1.46 mg g−1 respectively. CONCLUSION For both J. cordata and J. cardiophylla it could be inferred that (a) the oil and kernel meal were toxic and the kernel meal could be used as livestock feed only after detoxification, (b) the oil could be used for non‐alimentary purposes, i.e. biodiesel production, and (c) the seed or oil could be used for isolating various bioactive compounds for pharmaceutical and agricultural applications. © 2012 Society of Chemical Industry